Validation of ELISA Test-system for Trastuzumab (Herceptin, Hertikad) quantitative determination in biological fluids - V. V. Pisarev; A. V. Ivanov (Фармакокинетика и Фармакодинамика)
Relevance. Trastuzumab is the drug of choice for the HER2+ breast cancer treatment. To determine the trastuzumab pharmacodynamics in personalized therapy a validated bioanalytical method for measuring the concentration of the drug in biological fluids is required. The aim: creation and assessment of the suitability (validation) of a test system based on enzyme-linked immunosorbent assay (ELISA) for the quantitative determination of trastuzumab concentration in human serum/plasma. Materials and methods. The presented test system is a classic ELISA kit with a 96-well polystyrene plate, the wells of which are coated with monoclonal antibodies specific to trastuzumab, secondary goat antibodies to the Fc fragment conjugated with horseradish peroxidase (HRP), substrate solution — (3,5,3',5')-tetramethylbenzidine (TMB) and stop solution. Quality control solutions were prepared by diluting known concentrations of trastuzumab in blank serum. Results. In the course of the work the limit of detection (0.84 ng/ml) and the lower limit of quantitative determination (1.41 ng/ml) of trastuzumab in serum/plasma were established and the high selectivity of analyte determination in a multicomponent matrix was proved. The found average values of trastuzumab concentrations did not deviate from the nominal values by more than 14 % in the entire range of determined concentrations, the intraand interseries precision of the test system did not exceed 8%, and the total method error was 20.1 %. The demonstrated dilution linearity allows the assay to be used to analyze a wide range of trastuzumab concentrations in biological samples. The stability of the components of the test system is defined as at least 1 year under storage conditions. Conclusion. The presented ELISA test system complies with international validation requirements and it is suitable for practical use.